(untitled) (Prilozi za orijentalnu filologiju, 2017)
Phonetic realisation of nunation is a characteristic of the context form of the Standard Arabic Language, and its orthographic specificity is conditioned by the endeavour to escape the mixing with the same type of the final lexical or grammatical morpheme which is, for various purposes, suffixed to a word, and for the purposes of linguistic economy. At the phonological level and in the context form, nunation is an obligatory syllableforming element as a specificity of the Arabic language with respect to its orthography according to which it exists as one formally nonexistent consonant. From the aspect of meaning, nunation should not be interpreted as a standard mark of a non-definite name or as a case ending. It is a particular type of supplementary grammatical morpheme whose primary meaning is a three-case declension of a name, and it is only in form analogous to a case ending. At the morphological level of the word, nunation implies certain meanings on the basis of which its various types are defined, such as nunation of the three-case declension, of indefiniteness, correspondence, replacement, rhyme, information, need, excessiveness and the irregular nunation